Peran Karakter Dan Pola Pikir Dalam Membentuk Niat Berwirausaha: Tinjauan Literatur Sistematis - Kuncoro Aprilia Hikmawati; Yohanes Wibisono; Agung Winarno; Wening Patmi Rahayu (PT. Hasba Edukasi Mandiri, 2025)
This article discusses the role of character and mindset in shaping entrepreneurial intention, which is an important factor in starting and managing a business. This literature review examines 20 articles published between 2005 and 2023, using article selection techniques based on inclusion and exclusion criteria involving research relevant to the topics of entrepreneurship, character, and mindset. The method used is a systematic literature review with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) procedure to ensure rigor in the selection and evaluation of appropriate articles. The results of the literature review show that strong character traits, such as perseverance, creativity, and the courage to take risks, provide a solid foundation for individuals to face entrepreneurial challenges. On the other hand, a growth mindset encourages individuals to view failure as an opportunity to learn, rather than as an obstacle. Previous research indicates that these two factors are interrelated, where good character strengthens the growth mindset, and the growth mindset reinforces character. This article also suggests that entrepreneurship education should place greater emphasis on developing positive character traits and mindsets to enhance entrepreneurial intention, as well as the importance of social support in shaping individuals who are ready to face business challenges.